COFFEE FARMERS SATISFACTION ANALYSIS OF THE SEROKA JOINT MARKETING GROUP IN TIGADIHAJI DISTRICT, SOUTH OKU REGENCY - Masnadi; Fifian Permata Sari; Rini Efrianti (Bajang Institute, 2022)
This study aims to determine the level of satisfaction of robusta coffee farmers (Coffea robusta) in the joint marketing group (KPB Seroka) in TigaDihaji District, South OKU Regency. This study uses a quantitative descriptive method which will describe the condition of farmers. when conducting research by analyzing the income and satisfaction of robusta coffee farmers. The sample was taken by means of purposive sampling by means of direct interviews with members of the joint marketing group (KPB) which was seen in the marketing activities of robusta coffee as many as 77 heads of families of robusta coffee farmers (coffearobusta) at the research location. This research takes place from December 2021 to January 2022 and is located in TigaDihaji District, South OKU Regency. The data collected was analyzed to determine the satisfaction of farmers at KPB Seroka. The results showed that the level of satisfaction of KPB member farmers were quite satisfied with the services of the joint marketing group management.